A Bibliometric Analysis on ESG Risk and Financial Stability - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a bibliometric analysis of the intersection between Environmental, Social, and Governance (ESG) risk and financial stability, mapping the growth and development of research in this field. Utilizing data from Scopus, the analysis identifies key trends, influential publications, and emerging technologies within the ESG and finance domains. The study highlights the increasing recognition of ESG factors as essential to maintaining financial stability, with growing scholarly interest in integrating ESG risk into financial systems. Despite the global expansion of ESG research, certain regions, such as Turkey, Mexico, and Russia, exhibit less integration into the global network. This research aims to provide a comprehensive overview of the intellectual structure of ESG-related financial stability studies, offering insights into research gaps and future directions for policymakers, financial practitioners, and academics.